Complexation of synthetic CDM-AM copolymer with natamycin and carbendazim to improve solubility and fungicidal activity. (10th July 2015) - Li, Yong-Fu; Jin, Jing; Guo, Qin; Ha, Yi-Ming; Li, Qing-Peng
Highlights: CDM-AM copolymer was prepared by AM and CDM using K2 S2 O8 as initiator. The stability constant of NM·CDM-AM and MBC·CDM-AM were 10725.45 M −1 and 3000.89 M −1, respectively. The water-solubility of NM and MBC were increased 14-fold and 7.7-fold, respectively. The NM·CDM-AM and MBC·CDM-AM complexes had better fungicidal activity. Abstract: The β-cyclodextrin-acrylamide (CDM-AM) copolymer was prepared from acrylamide and β-CD maleate (CDM) using K2 S2 O8 as initiator. The effects of the CDM-AM copolymer on the solubility and fungicidal activity of natamycin (NM) and carbendazim (MBC) were investigated. The stability constant of NM·CDM-AM and MBC·CDM-AM complexes at 303 K were of 10, 725.45 M −1 and 3000.89 M −1, respectively. The complexes were characterized using phase solubility diagrams, NMR spectra and FT-IR spectra. The analysis of the biological activities of these two complexes indicated that they possessed enhancing fungicidal activities compared to NM and MBC alone.